2001
DOI: 10.1007/bf03190396
|View full text |Cite
|
Sign up to set email alerts
|

Gender difference in ifosfamide metabolism by human liver microsomes

Abstract: Pharmacokinetic gender-dependent differences in cytochrome P450-mediated drug metabolism, especially CYP3A4, and their clinical implications are increasingly apparent. CYP3A4 seems to be the most important CYP isoform in both bioactivation and N-dechloroethylation of the alkylating prodrug ifosfamide, but informations about possible gender-related differences are lacking. Therefore we compared in 10 male and 10 female liver microsomal preparations the contents and activities of specific isoenzymes, involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 28 publications
(16 reference statements)
2
40
0
Order By: Relevance
“…1, model 1). 20) A similar tendency observed in in vitro studies using human liver microsomes has been reported by other groups, [21][22][23][24] while studies that failed to detect female dominance have also been reported. [25][26][27][28] Assessment of CYP3A activity in vivo has been carried out by measuring the clearance of various CYP3A substrates.…”
Section: Sex Difference Of Cyp3a4supporting
confidence: 78%
“…1, model 1). 20) A similar tendency observed in in vitro studies using human liver microsomes has been reported by other groups, [21][22][23][24] while studies that failed to detect female dominance have also been reported. [25][26][27][28] Assessment of CYP3A activity in vivo has been carried out by measuring the clearance of various CYP3A substrates.…”
Section: Sex Difference Of Cyp3a4supporting
confidence: 78%
“…Comparatively, the same antibody detected levels of CYP3A in female liver microsomes, which has been demonstrated to be significantly higher than in male samples, amounting to 141 and 69 pmol mg protein À1 (median; P ¼ 0.038, Mann -Whitney rank sum test), respectively ( Figure 6) (Schmidt et al, 2001). The use of a CYP3A5-specific antibody allowed us to exclude the expression of CYP3A5 in the tested tumours, but the involvement of CYP3A7 could not be further clarified because of the absence of a specific anti-CYP3A7 antibody.…”
mentioning
confidence: 81%
“…Accordingly, certain CYP3A4 drug substrates, including cyclosporine (Kahan et al, 1986), erythromycin (Austin et al, 1980), and nifedipine (Krecic-Shepard et al, 2000), show higher clearance rates in women. CYP3A4-catalyzed hepatic microsomal N-dechloroethylation of the anticancer drug ifosfamide is also more rapid in women, suggesting that women could be more susceptible to the neurotoxic side affects associated with this metabolic pathway (Schmidt et al, 2001). CYP3A4 also metabolizes steroids, such as cortisol, whose conversion to 6␤-hydroxycortisol is more rapid in women than in men and serves as a biomarker for CYP3A4 metabolic activity (Inagaki et al, 2002).…”
Section: Sex Differences In Hepatic Drug Metabolismmentioning
confidence: 99%